Spiritualitas Iman Katolik sebagai Fondasi Resiliensi Mahasiswa dalam Kehidupan Akademik - Kristiana Mendrofa (STP Dian Mandala Gunungsitoli Nias Keuskupan Sibolga, 2025)
This article aims to analyze the role of the spirituality of the Catholic faith as the foundation of student resilience in facing the dynamics of academic life. The research uses the literature review method by examining reputable Church documents, books, and articles. The results of the study show that student resilience does not only come from psychological and social factors, but gains depth when supported by the spiritual dimension. Catholic spirituality lived through prayer, sacraments, devotion, and involvement in the community of faith provides meaning in suffering, transcendent strength, and social support that strengthen students' resilience. The integration of resilience and spirituality makes academic life not only an arena for intellectual achievement, but also a space for faith growth and spiritual maturity. Thus, the spirituality of the Catholic faith serves as a foundation that helps students not only survive academic pressure, but also develop into hopeful individuals who are ready to contribute to the Church and society.